ANALISIS STRATEGI PENGELOLAAN AGROWISATA DI KAMPUNG AIR MANDIDI DISTRIK TELUK KIMI, KABUPATEN NABIRE PAPUA TENGAH - Dasnarebo, Simson Semuel Hwat; Roy, Marloza (Jurnal FAPERTANAK : Jurnal Pertanian dan Peternakan, 2024)
The development and enhancement of agrotourism in Air Mandidi Vilage, Teluk Kimi District, Nabire Regency, Central Papua Province, is based on the potential of natural resources and agricultural prospects that can serve as attractions for tourism. Research conducted over approximately one month in Air Mandidi vilage showed positive responses toward the development and management of agrotourism initiatives. The SWOT analysis reveals significant strengths such as the availability of 50 hectares of agricultural land, support from local government and communities, and ecological wealth including hot springs and lakes, which enhance tourism appeal. However, weaknesses like inadequate road infrastructure and insufficient tourist accommodations need addressing. Opportunities exist with the rising demand for organic farming and government support programs, while threats include competition from other agrotourism sites and environmental changes affecting agriculture. Internal and external factor analyses (IFAS and EFAS) indicate a solid foundation for developing agrotourism, highlighting the necessity for strategic plans that leverage strengths and opportunities while mitigating weaknesses and threats. The overall findings underline the potential for sustainable growth in agrotourism in Air Mandidi Vilage, contingent upon effective management and community involvement.